Representation of Pancasila Values to Millenials (Case Study at Genesis Medicare Health Polytechnic) - Marcel Haggai (Jurnal Mantik, 2021)
Entering the era of globalization as it is today, changes in various sectors are indeed running very fast, this is caused by the increase in various cultures and patterns of life that greatly affect a nation. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the increasing development of information and communication makes all aspects of the world experience a very competitive transition of meaning, and as we know that the effects caused by this era of globalization have reached At the level of the next generations of the Indonesian nation, slowly a new culture begins to form and intersect with several national ideologies, one of which is the loss of Pancasila values in the life of the nation and state, as one of the most valuable cultural heritages, the position of Pancasila values gradually begin to erode with changing times, so to restore the image of Pancasila as the nation's ideology, it is necessary to instill a basic understanding of the nation's generation to care for and practice every meaning contained in Pancasila.